The participation of Wajãpi women from the State of Amapá (Brazil) in the traditional use of medicinal plants - a case study - da Mata Nely Dayse Santos; de Sousa Rosinaldo Silva; Perazzo Fábio F; Carvalho José Carlos Tavares (BMC, 2012)
Abstract Background The purpose of this study was to analyze the importance of traditional medicinal plants use to Wajãpi women in the State of Amapá, Brazil, as well as their practices in the local common illnesses of treatment considering the prevailing practice by non-Indians. Methods This study was conducted in the Community of the Wajãpi Indigenous People, a Brazilian territory located in the central western State of Amapá. Wajãpi women were selected for the interview since they have the responsibility to harvest, collect and prepare the preparations. The studied women were residents of four villages. The number of women within these four villages is 24. Results and conclusions The findings fell into the following three categories: 1) The daily use of medicinal plants by women and main methods of application. In this category, the botanical families found included Leguminosae-Caesalpinoideae, Anacardiaceae, Meliaceae, and Rubiaceae. The main forms of use found were teas, baths, maceration, in natura, and juices; 2) Through analysis of illness and treatment records, a lack of knowledge integration in the health system was shown to be due to a variety of gaps and the need of health professionals to be more aware about the local culture which they intend to work with, what could decrease the prevailing barriers between the social groups involved; 3) Traditional knowledge and possible sustainability can be fostered by stimulating the transmission of traditional knowledge from generation to generation, therefore reducing the dependence on industrialized medicines and also by maintaining an appreciation of those practices among youngsters, who tend to question them.